Competitiveness and Competitive Advantages of Enterprises in the Energy Sector - Kapitonov, Ivan A.; Zhukovskaya, Irina V.; Khusaenov, Rustem R.; Monakhov, Valentin A. (International Journal of Energy Economics and Policy, 2018)
Traditional energy sources form the basis of the energy complex. But the use of renewable energy sources is more acceptable from the ecological point of view and contributes to the saving of oil and gas resources. Therefore, the authors analyzed the competitiveness of the use of alternative energy sources. To study the issue, the study used econometric, theoretical methods. It was found that most of the energy resources in the world and in the Russian Federation is covered by gas and oil, but alternative energy sources are gaining momentum. It is determined that in Russia the greatest percentage is occupied by bio-heat power stations, while in the world the main part is given to wind energy. Keywords: Power Complex, Wind Power, Competition, Renewable Energy, Large Business. JEL Classifications: P18, P28.